Photodegradation of 2,4,6-Trinitrotoluene and Nitrobenzene Mixtures in TiO2 Suspensions and Their Use for Treatment of Wastewater - Van Chat, Nguyen; Ngoc Khue, Do; Van Hung, Nguyen; Van Chung, Tran; Francis Cheng, I. (Asian Journal of Chemistry, 2010)
The photo catalytic oxidation of nitrobenzene and 2,4,6-trinitrotoluene mixture in aqueous suspensions of titanium dioxide (TiO2 Degussa type P25) was investigated. Under oxygen conditions, irradiation with the pyrex-filtered out put of 15 W high pressure mercury-arc lamp resulted in complete (more 90 %) mineralization of 50 ppm of 2,4,6-trinitrotoluene, 30 ppm of nitrobenzene within few hours. At the beginning irradiation, reduction by conduction band electrons may play a more significant role in the photo catalytic degradation of the studied mixtures. The resulted in aromatic amine compounds were more easily to be oxidized by the hydroxyl radicals.